An investigation into the dynamics of corporate ikonogenics in the South African corporate environment and the development of a marketing model for the management of corporate image - Hugo, M. M.(Maria Magdalena) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D) -- University of Stellenbosch, 1992.